Chemical Castration For Sexual Violance Convicts In Indonesia: The Hifz al-Nafs and Huquq al-Insan Review - Sanuri, M (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
The number of sexual harassment against children and women in Indonesia has increased significantly. This shows that women and children are currently insecure. To respond to this, the Indonesian government came up with Law Number 23 of 2002, Government Regulation in Lieu of Law Number 1 of 2016, Law Number 17 of 2016, and Government Regulation Number 70 of 2020 to eliminate the increasing number of victims and provide a deterrent effect for perpetrators. On the other hand, there have been pros and cons from all levels of Indonesian society regarding the chemical castration punishment. To consider the effectiveness of chemical castration, this study will look at the perspective of hifz al-nafs (guarding the soul) and huquq al-insan (human rights) as the basic rights that should not be violated. The results of the research showed that chemical castration is effective because it is able to provide maslahah values ​​in the form of a deterrent effect for perpetrators and security and safety especially for children and women, although there are few problems in the area of ​​human rights, where perpetrators of sexual crimes have the right to be treated fairly before the law.